Maxillary and Mandibular First Premolars Showing Three-Cusp Pattern: An Unusual Presentation. (12th February 2013) - Nayak, Ramakant; Kotrashetti, Vijayalakshmi; Nayak, Aarati; Patil, Viraj; Kulkarni, Mayuri; Somannavar, Pradeep; Hosmani, Jagadish
Abstract : Dental anatomy is the study of morphology of various teeth in human dentitions. The application of dental anatomy in clinical practice is important, and dentist should have a thorough knowledge regarding the morphology of the teeth. At times as a result of genetic variation, environmental factors, diet of an individual and race, variations in the morphology of the teeth can be observed. These variations have been extensively studied by the researcher in the field of anthropology to define a particular race. The most commonly observed changes include peg-shaped laterals, shovel-shaped incisors, and extra cusp on molar. Common variations documented with regard to maxillary and mandibular first premolars are the variation in the number of roots. But the variations with respect to crown morphology are few. We report a first documented unusual presentation of maxillary and mandibular first premolars with three-cusps pattern in a female patient.